Challenges in Laboratory Data Management for Telemedical Services - Annor Owusu, Lilias; Koshechkin, Konstantin (Universitas Muhammadiyah Semarang, 2025)
Background: The practice of providing clinical care remotely via electronic communications is known as telemedicine.Objective: To improve patients' health, the World Health Organization (WHO) created the term in the 1970s to describe a legitimate method of exchanging medical information about diagnosing, treating, and preventing illness and injury through information and communication technology. Result: The notion of telemedicine is not a novel one. In both wealthy and underdeveloped nations, telemedicine is a cutting-edge idea that is expanding. ICT, or information and communication technology, is a significant factor in improving healthcare at the individual and community levels.Conclusion: Today,